Practicability of the bulk procurement of petroleum products and single receiving point: Perspectives from selected stakeholders. - Chacha, Clement Marwa. (Mzumbe University, 2024)
Dissertation Submitted to Mzumbe University Dar es Salaam Campus College (MUDCC) in Partial Fulfillment of the Requirements for Award of the Degree of Master of Business Administration in Corporate management (MBA-CM.) of Mzumbe University